Hypocholesterolemia in patients with an amebic liver abscess - Flores, María S.; Obregón Cárdenas, Adriana; Tamez, Eva; Rodríguez Pérez, Elba Guadalupe; Arévalo Niño, Katiushka; Quintero Zapata, Isela; Tijerina Menchaca, Rolando; Bosques Padilla, Francisco Javier; Galán Wong, Luis Jesús (2014)
Background/Aims: Many parasites induce changes in the lipid profiles of the host. Cholesterol increases the virulence of Entamoeba histolytica in animal models and in vitro culture. This study aimed to determine, in patients with an amebic liver abscess, the correlation between cholesterol and other features, such as the size and number of abscesses, standard hematological and serum chemistry profiles, liver tests, and duration of hospital stay. Methods: A total of 108 patients with an amebic liver abscess and 140 clinically healthy volunteers were investigated. Cholesterol and triglycerides were measured in the sera. The data from medical observations and laboratory tests were obtained from the clinical records. Results: A total of 93% of patients with an amebic liver abscess showed hypocholesterolemia not related to any of the studied parameters. Liver function tests correlated with the size of the abscess. The most severe cases of amebic liver disease or death were found in patients whose cholesterol levels continued to decrease despite receiving antiamebic treatment and hospital care. Conclusions: Our results show that the hypocholesterolemia observed in patients with an amebic liver abscess is not related to any of the clinical and laboratory features analyzed. This is the first study relating hypocholesterolemia to severity of hepatic amebiasis.